ChemInform Abstract: Acetamide/SO2Cl2 as an Efficient Reagent for Friedel—Craft′s Acylation of Aromatic Compounds under Ultrasonic and Microwave Conditions. Issue 33 (19th August 2014) - Satish Kumar, Mukka; Chinna Rajanna, Kamatala; Venkanna, Purugula; Venkateswarlu, Marri
Abstract Friedel—Craft′s acetylation of aromatic compounds by acetamide/SO2Cl2 proceeds under microwave irradiation in high yields and short reaction times.